Long-term outcome of patients with myocardial infraction with nonobstructive coronary arteries. (14th October 2021) - Barrett, O; Edry Nadiv, O; Peles, I; Abramowitz, Y; Cafri, C; Rosenstein, G; Merkin, M; Zahger, D; Koifman, E
Abstract: Background: Myocardial infarction with nonobstructive coronary arteries (MINOCA) is a condition of growing interest and research. We aimed to evaluate the long-term prognosis of MINOCA patients and identify possible risk factors associated with long term mortality in this patient's population. Methods: We performed a retrospective observational cohort study including all patients aged ≥18 years hospitalized to a large tertiary center between 2005–2018 with a primary diagnosis of acute myocardial infarction (AMI) and non-obstructive lesions with less than <50% stenosis in all coronary arteries. The aim of the study was to assess the long-term mortality and to evaluate factors associated with increased mortality in this population. Results: MINOCA was diagnosed in 1544 patients during the study period. Mean age of patients was 61±12.3 and 46% were female. Common comorbidities were dyslipidemia (32.6%) and hypertension (21.2%) and 17% had prior PCI. More than third of the patients were treated with statins (37.2%), micropirin (32.7%) and angiotensin converting enzyme (ACE)-inhibitors (30.4%). While short-term prognosis was favorable with only 1.2% mortality at 30-days, 1-year mortality was 3.9% and 19.9% mortality at mean follow-up time of 8.5 years. While many factors were associated with unfavorable long-term outcome in the univariate analysis, only advanced age (HR =1.05, 95% confidence interval (CI) 1.02–1.07; p<0.001) and congestive heart failure (HR=3.53, 95% CI 1.74–7.18; P<0.001) were independently associated with increased mortality risk in the adjusted model. Conclusions: MINOCA is not an infrequent condition that carries a good short-term outcome, but long-term outcome may be comparable to patients with obstructive coronary disease. Further research should be performed to elucidate the various mechanisms of MINOCA. Funding Acknowledgement: Type of funding sources: None.